Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm having problems with the following expression:

(A'+B)'+B(A'+AC)+ABC'

And here is what I tried to simplify:

AB' + B(A'+AC) + ABC' (De Morgan's)
AB' + B(A'+C) + ABC' (Identity)
AB' + A'B + BC + ABC' (Distribuitive)

Here I convert to Standard SOP Form (first term is missing C or C'; second term is missing C or C'; third term is missing A or A')

I run this on Karnaugh maps, and final result is: A+B

For the Identity rule, I read: Boolean Simplification of A'B'C'+AB'C'+ABC'

(A'+AB = A'+B)

The problem is, this doesn't seem to be right if I follow this tool: http://www.eecis.udel.edu/~roman/simplifier/Function.html

What exactly am I doing wrong here?

share|improve this question
    
Hint: Does $A'B+BC+ABC' = B(A'+C+AC') = B(A' + (C+C'A))$ lead to any simplification? –  Dilip Sarwate Sep 6 '12 at 13:09
    
(C+C'A) = C+A, correct? I'm still getting the same result though. –  Joao Ferreira Sep 6 '12 at 13:32
    
Perseverance, perseverance, perseverance! You got $B(A'+(C+C'A)) = B(A'+C+A)$, right? Is $A'+C+A$ the same as $A'+A+C$? Can you simplify that? –  Dilip Sarwate Sep 6 '12 at 14:24
    
Ok, B(A′+A+C)= B(1+C) = B(1) = B; so now my Expression is AB' + B which results in A(B'+B) = A(1) = A... –  Joao Ferreira Sep 6 '12 at 15:01
    
$AB' + B = A(B'+B)$? Which law are you using here? –  Dilip Sarwate Sep 6 '12 at 15:26

3 Answers 3

up vote 2 down vote accepted

We'll start with the most obvious simplifications.

$(A' + B')' + B(A' + AC) + ABC'$

$AB' + B(A' + C) + ABC'$

$AB' + BA' + BC + ABC'$

$A(B' + BC') + BA' + BC$

$A(B' + C') + BA' + BC$

$AB' + AC' + A'B + BC$

At this point the expression cannot be obviously reduced further. The secret is to use the consensus theorem to introduce redundancy. The consensus theorem states that $XY + X'Z + YZ = XY + X'Z$ If we set $XY = A'B$ and $X'Z = AC'$ then our expession becomes

$AB' + AC' + A'B + BC +BC'$

From here we can do the standard reductions.

$AB' + AC' + A'B + B$

$AB' + AC' + B$

$A + B + AC'$

$A + B$

share|improve this answer
    
Cheers for your help, seems the online tool is giving out the wrong result then... –  Joao Ferreira Sep 6 '12 at 16:45

$(A'+B)'+B(A'+AC)+ABC'=AB'+BA'+BAC+ABC'=AB'+BA'+AB(C+C')=AB'+BA'+AB=AB'+B(A+A')=AB'+B=A+B$

share|improve this answer
(A'+B)'+B(A'+AC)+ABC'
=  (A'+B)'+B(A'+C)+ABC'         by absorption [ A'+AC  =  A'+C ]
=  (A)(B')+B(A'+C)+ABC'         by DeMorgan [ (A'+B)'  =  (A)(B') ]
=  (A)(B')+(BA'+BC)+ABC'        by distributivity [ B(A'+C)  =  (BA'+BC) ]
=  AB'+BA'+BC+ABC'      by associativity
=  AB'+A'B+BC+ABC'      by commutativity
=  AB'+AC'+A'B+BC       by absorption [ AB'+ABC'  =  AB'+AC' ]
=  A'B+AB'+BC'+BC       by consensus [ AB'+AC'+A'B  =  A'B+AB'+BC' ]
=  A'B+AB'+B        by absorption [ BC'+BC  =  B ]
=  B+AB'        by absorption [ A'B+B  =  B ]
=  A+B      by absorption [ B+AB'  =  A+B ]

Answer: A+B

Using tool at www.logicminimizer.com

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.